The role of tax assessment in the fight against criminal phenomena (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The paper addresses the potential role that the assessment activity carried out by the Tax Administration can play in the fight against criminal phenomena. By reconstructing the main assessment tools at both national and international levels, the Author examines the possible contacts and the inter-institutional synergies that may be established between the Tax Administration and the Criminal Justice Authority.
Keywords: Tax Administration; assessment activities; criminal phenomena; exchange of information; international evasion and tax avoidance